PENGARUH MODAL INTELEKTUAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP NILAI PERUSAHAAN PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fadlun, Fadlun (Katalogis, 2016)
The purpose of this research is to define and analyze the influence of Intellectual Capital and Institutional Ownership on Company’s value in the Food and Beverage industries in Indonesia stock exchange. Population of the research consists 0f 16 food and beverage industries in Indonesia stock exhange, and its sample is selected through purposive sampling; there are 12 industries that meet the requirements of this study. Data analysis is using multiple linier regressions. The study finds that :1) capital intellectual and institutional ownership simultaneously have no influence on the value of companies in food and beverage industries in indonesia stock exchane; 2)intellectual capital partially has no influence on the value of companies in food and beverage industries in indonesia stock exchane; (3) Institutional ownership partially has no influence on the value of companies in food and beverage industries in indonesia stock exchane. Determination coefficient (R2) off 0,011 showsthat 1,1 % variable intellectual capital and institutional ownership influence the companies’ values, while 98,8 % by other variables that are not studied